Training and Mentoring for the "Masterpiece Program for Strengthening Patriotism" for Elementary School Teachers, Parents, and Students at the Indonesian School in Yangon, Myanmar - Emmanuel Kus Eddy Sartono; Hendra Prasetia; Fathurrohman Fathurrohman; Suparlan Suparlan (International Journal of Public Devotion, 2026)
The training program on character-building for patriotism for primary school teachers, parents, and students at the Indonesian School in Yangon, Myanmar, is very important to conduct. This training aims to train the skills of Indonesian elementary school teacher human resources in Yangon, Myanmar, so that they are able to carry out learning activities through a showcase that can increase love for the homeland. The showcase training to strengthen love for the homeland character was conducted in a hybrid manner (online and face-to-face). The showcase training program to strengthen love for the homeland character for teachers, students, and parents of students at the Indonesian school in Yangon, Myanmar, which included an introduction to Indonesian culture such as traditional clothing, traditional houses, and traditional weapons, increased knowledge and attitudes of love for the homeland by 88% based on the results of the post-test. From this training, teachers, parents, and students will develop their knowledge, insights, and attitudes, and will foster a love for their homeland, Indonesia.   Pelatihan dan Pendampingan untuk "Gelar Karya Penguatan Cinta Tanah Air" bagi Guru, Orang Tua, dan Siswa Sekolah Indonesia Yangon, MyanmarABSTRAKPelatihan program gelar karya penguatan karakter cinta tanah air bagi guru, orang tua dan siswa SD di Sekolah Indonesia Yangon Myanmar sangat penting dilaksanakan. Pelatihan ini bertujuan untuk melatih skill SDM guru SD Indonesia Yangon di Myanmar agar mampu melaksanakan kegiatan pembelajaran melalui gelar karya yang dapat meningkatkan kecintaan terhadap tanah air. Pelatihan gelar karya penguatan karakter cinta tanah air dilaksanakan dilaksanakan secara hybrid (secara online dan tatap muka), Program pelatihan gelar karya penguatan karakter cinta tanah air bagi guru, siswa dan orangtua siswa di sekolah Indonesia Yangon Myanmar, mencakup pengenalan budaya Indonesia seperti pakaian tradisional, rumah tradisional, dan senjata tradisional meningkatkan pengetahuan dan sikap cinta tanah air sebesar 88% dari hasil post test. Dari pelatihan ini, guru, orang tua, dan siswa berkembang pengetahuan, wawasan dan sikap mereka, akan kecintaan terhadap tanah air Indonesia.Kata Kunci :Pelatihan; Gelar karya; penguatan karakter; cinta tanah air.